Use of Smokeless Tobacco Before Conception and Its Relationship With Maternal and Fetal Outcomes of Pregnancy in Thatta, Pakistan: Findings From Women First Study. Issue 8 (21st October 2020) - Aziz Ali, Sumera; Khan, Umber; Abrejo, Farina; Vollmer, Brandi; Saleem, Sarah; Hambidge, K Michael; Krebs, Nancy F; Westcott, Jamie E; Goldenberg, Robert L; McClure, Elizabeth M; Pasha, Omrana
Abstract: Introduction: Smokeless tobacco (SLT) consumption during pregnancy has adverse consequences for the mother and fetus. We aimed to investigate the effects of maternal pre-pregnancy SLT consumption on maternal and fetal outcomes in the district of Thatta, Pakistan. Aims and Methods: We conducted a secondary data analysis of an individual randomized controlled trial of preconception maternal nutrition. Study participants were women of reproductive age (WRA) residing in the district of Thatta, Pakistan. Participants were asked questions regarding the usage of commonly consumed SLT known as gutka (exposure variable). Study outcomes included maternal anemia, miscarriage, preterm births, stillbirths, and low birth weight. We performed a cox-regression analysis by controlling for confounders such as maternal age, education, parity, working status, body mass index, and geographic clusters. Results: The study revealed that 71.5% of the women reported using gutka, with a higher proportion residing in rural areas as compared with urban areas in the district of Thatta, Pakistan. In the multivariable analysis, we did not find a statistically significant association between gutka usage and anemia [(relative risk, RR: 1.04, 95% confidence interval, CI (0.92 to 1.16)], miscarriage [(RR: 1.08, 95% CI (0.75 to 1.54)], preterm birth [(RR: 1.37, 95% CI (0.64 to 2.93)], stillbirth [(RR: 1.02, 95% CI (0.39 to 2.61)], and low birth weight [(RR: 0.96, 95% CI (0.72 to 1.28)]. Conclusions: The study did not find an association between gutka usage before pregnancy and adverse maternal and fetal outcomes. In the future, robust epidemiological studies are required to detect true differences with a dose–response relationship between gutka usage both before and during pregnancy and adverse fetomaternal outcomes. Implications: While most epidemiological studies conducted in Pakistan have focused on smoking and its adverse outcomes among males, none of the studies have measured the burden of SLT among WRA and its associated adverse outcomes. In addition, previously conducted studies have primarily assessed the effect of SLT usage during pregnancy rather than before pregnancy on adverse fetal and maternal outcomes. The current study is unique because it provides an insight into the usage of SLT among WRA before pregnancy and investigates the association between pre-pregnancy SLT usage and its adverse fetomaternal outcomes in rural Pakistan.